A review of indications and comorbidities in which warfarin may be the preferred oral anticoagulant. (4th January 2021) - Wadsworth, Daniel; Sullivan, Emma; Jacky, Thomas; Sprague, Taylor; Feinman, Hannah; Kim, Jennifer
Abstract: What is known and objective: Direct oral anticoagulants (DOACs) are increasingly prescribed instead of warfarin for chronic anticoagulation for ease of dosing, fewer interactions, and less stringent monitoring. However, it is important to consider indications and comorbidities for which warfarin is still the preferred anticoagulant. This review aims to capture these clinical scenarios in which warfarin may still be preferred over DOACs. Methods: We undertook a comprehensive literature search using the PubMed database. Key search terms were based on DOAC clinical trial exclusion criteria, as well as indications and conditions in which the use of DOACs for anticoagulation has suggested harm. Society guidelines and tertiary literature were used to inform expert opinion where necessary. Studies were included if they investigated the use of DOACs or warfarin in the identified indications or conditions. Results and Discussion: Currently, evidence for the use of warfarin over DOACs for anticoagulation is strongest for patients with prosthetic valves, antiphospholipid syndrome, or a high risk of gastrointestinal bleeding. For several clinical situations, including mitral stenosis, obesity, altered gastrointestinal anatomy, pulmonary arterial hypertension, renal or hepatic impairment, and left ventricular thrombus, evidence is lacking but may eventually support the use of DOACs. Depending on indication and condition, appropriateness of DOAC use may vary by agent. What is new and conclusion: New evidence continues to support new indications and conditions in which DOACs may be appropriate to use for anticoagulation. There are key clinical scenarios, however, in which emerging literature continues to support warfarin as the preferred anticoagulant.